Answered

Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Solve the given system, using the substitution method.

y = 3x – 4
9x – 3y = 14


Sagot :

naǫ
[tex]y=3x-4 \\ 9x-3y=14 \\ \\ \hbox{substitute 3x-4 for y in the 2nd equation:} \\ 9x-3(3x-4)=14 \\ 9x-9x+12=14 \\ 12=14 \\ not \ true \\ \\ \boxed{\hbox{no solution}}[/tex]